Leadership Perspectives Among Diaspora Evangelicals in the USA: The Interplay of Theology, Self-Discipline, and Spiritual Maturity - Negrov, Aleksandr I. (Bogoslovs'ki rozdymi, 2025)
This article examines perspectives on leadership and leadership development among Evangelicals in the so-called Slavic diaspora of the United States, with particular attention to the interplay of theology, self-discipline, and spiritual maturity. The study is based on data from 173 participants - 36 interviewees and 137 survey respondents - drawn primarily from Ukrainian diaspora churches, alongside Christians who migrated from Russia, Belarus, Moldova, and Central Asia. Data were collected between April 2021 and May 2025 within educational processes initiated by churches or non-accredited educational organizations in the United States. The findings indicate that participants consistently affirm spiritual growth and intimacy with God as foundational to leadership. At the same time, many acknowledge that insufficient self-discipline constitutes a significant obstacle to their formation as leaders. Leadership was frequently described in social or functional terms - such as organizational effectiveness or communal influence - rather than in explicitly theological categories. Moreover, a majority of respondents gave little attention to the role of followership, revealing a notable gap in holistic reflection on leadership. The article argues that an integrated approach - linking theological reflection with disciplined leadership practice - is essential for cultivating spiritually grounded, ethically responsible, and effective leaders and followers. Such integration is particularly crucial for immigrant evangelical communities as they navigate questions of identity, cultural adaptation, and mission in the American context.